The Bay of Pigs - Jones, Howard, 1940- (Pivotal moments in American history., 2008)
Jones provides a concise, incisive, and dramatic account of President Eisenhower's disastrous attempt to overthrow Fidel Castro. He deftly examines the train of missteps and self-deceptions that led to the invasion of U.S.-trained exiles at the Bay of Pigs.